A democratização da gestão na educação superior: uma análise do processo de sucessão dos dirigentes universitários da Universidade Federal de Uberlândia entre 2000 e 2005 - Souza, Ana Cecília Jorge de (2007)
This study has as objective generality to analyze the effective system of succession of controllers of the UFU, with the concerns to understand and to evaluate its importance for the process of democratization of the university management from the historical analysis, of the current politics for the public superior education and of its internal reorganization, emphasizing the questions of autonomy, decentralization and participation in the period of 2000 the 2005. The study proposal was developed by means of analysis of the category-key while pillars of the process of democratization of the educational management in which if it inserts the Federal University of Uberlândia. One is about the analysis of the management in a situated federal university in the Southeastern region, the State of Minas Gerais. In the development of the several nuances and dimensions that the educational management presents and that the democratic management is demanded, the element that if places in the studies on the thematic one is to look for to understand for where it walks the dimension and the means of the democratization of the management in the superior education. The way covered for the development of the work was the accomplishment of a field research, opting itself to the qualiquantitative methodological boarding, that allows to more than appeal the one technique of collection of data. In the quantitative research, of objective analysis, an inter locution with the qualitative research occurs, of subjective analysis, so that if it can better translate the intention and the approach of the study. Ahead of the facts, it was considered that it had an advance in the process of participation in the elections in the scope of the university, but that act to only vote does not mean that has democratic management. A democratic management also passes for the management of the processes and the results with the user, external intern and, as well as the relation of the UFU in the community that represents and that it represents it. Therefore, ahead of the answers of the involved citizens in the research, one becomes necessary to have conscience of that it needs to go beyond the management model, that is, the model starts to be accessory, what it is considered is the capacity to know to lead the university are practised through the practical managements and not substituted by action and goals that move from time to time.